Efficacy of lymph node dissection during robotic-assisted lobectomy for non-small cell lung cancer: retrospective review of 159 consecutive cases - Velez-Cubian, Frank O.; Rodriguez, Kathryn L.; Thau, Matthew R.; Moodie, Carla C.; Garrett, Joseph R.; Fontaine, Jacques P.; Toloza, Eric M. (Journal of Thoracic Disease; Vol 8, No 9 (September 28, 2016): Journal of Thoracic Disease, 2016)
Background: We investigated whether robotic-assisted surgery improves mediastinal lymph node dissection (MLND). Methods: We analyzed patients (pts) who underwent robotic-assisted video-assisted thoracoscopic surgery (R-VATS) lobectomy for non-small cell lung cancer (NSCLC) over 36 months. Perioperative outcomes, tumor histology, numbers, locations, and status of all lymph nodes (LNs), and TNM (tumor, nodal, and metastasis) stage changes were analyzed. Results: One hundred fifty-nine pts had mean tumor size 3.3±0.2 cm, most commonly being adenocarcinoma. Assessment of ≥3 N2 stations occurred in 156 (98.1%) pts, with 141 (88.7%) pts having >3 N2 stations reported. Mean total N1 + N2 stations assessed was 5.6±0.1 stations, including mean 4.1±0.1 N2 stations assessed. Mean N2 LNs reported was 7.2±0.3 LNs, and mean total N1 + N2 LNs reported was 13.4±0.4 LNs. There were 118 (74.2%) clinical stage-I pts versus 96 (60.4%) pathologic stage-I pts. Overall, 48 (30.2%) pts were upstaged, including 13 pts with cN0–pN1, 13 pts with cN0–pN2, 4 pts with cN1–pN2, and 18 pts with changes in T. Conclusions: R-VATS lobectomy is safe and results in perioperative outcomes comparable to those reported for conventional VATS. R-VATS MLND is effective at detecting occult metastatic disease during lobectomy for NSCLC.